An Exploration of Sustainable Customer Value and the Procedure of the Intelligent Digital Content Analysis Platform for Big Data Using Dynamic Decision Making - Wang, Shen-Tsu (Asian Journal of Economics and Empirical Research, 2016)
The dynamic Parasuraman, Zeithaml and Berry (PZB) service quality model is applied in the analysis of different customer clusters of sustainable customer value, while considering enterprise sustainability, customer relationship management (CRM), and customer equity of customer satisfaction and customer value. Based on intelligent digital content analysis and the recommendation platform of the different customer clusters of sustainable customer value, the dynamic six-sigma method is applied to the leisure agriculture of sustainable key resources and procedures solutions, as well as the impact of environmental and social costs and benefits. Based on the leisure agriculture of sustainable key resources and procedures solutions, the sustainable contradictions of leisure ecotourism agriculture are considered using dynamic multi-criteria decision making (dynamic gray multi-attribute decision making and dynamic multi-objective planning) to analyze the optimal plan for balancing the leisure agriculture of ecotourism and sustainable contradictions. First, sustainable and local identification plans are developed by the dynamic grey multi-attribute decision making method. Next, dynamic multi-objective planning is developed, as based on the priority factors sorted by gray multi-attribute decision making, in order to carry out the decision-making analysis of different objectives under different situations; thereby, helping the development of featured sustainable customer value of local leisure agriculture.